Android security essentials LiveLessons (sneak peek video training) - Nolan, Godfrey; Safari eBooks ([S.l.] : Addison-Wesley Professional Pearson, 2013)
"Android applications make use of advanced hardware and software, as well as local and server data, exposed through the platform to bring innovation and value to consumers. To protect that value, the platform must offer an application environment that ensures the security of users, data, applications, the device, and the network. Securing an open platform requires a robust security architecture and rigorous security programs, as well as developers who are aware of the security issues that may come up. Android Security Essentials LiveLessons alerts developers to the security issues that can arise when using the Android platform and guides them though solutions. Godfrey Nolan covers best practices for Android security by examining common security scenarios. Each lesson begins by presenting the concept behind the security problem at hand, with snippets of code introduced as the problem is explored. This is then followed by examination of code or demonstration of tools showing you how to implement the concepts presented. Godfrey Nolan is founder and president of RIIS, a mobile development firm in the Detroit metro area. Godfrey has spoken at AnDevCon, JavaOne, ASP-Connections, VSLive, CodeMash, Code PaLOUsa, 1DevDay, and many local Java and .NET user groups on a wide range of topics, including continuous integration, executable requirements and mobile security."--Resource description page.
Title from resource description page (viewed Feb. 18, 2014).
Presenter, Godfrey Nolan.
Keywords: Android (Electronic resource); Computer security; Electronic books